Challenges in Modelling Hypoglycaemia-Associated Autonomic Failure: A Review of Human and Animal Studies. (23rd October 2016) - Senthilkumaran, Manjula; Zhou, Xin-Fu; Bobrovskaya, Larisa
Abstract : Recurrent insulin-induced hypoglycaemia is a major limitation to insulin treatment in diabetes patients leading to a condition called hypoglycaemia-associated autonomic failure (HAAF). HAAF is characterised by reduced sympathoadrenal response to subsequent hypoglycaemia thereby predisposing the patients to severe hypoglycaemia that can lead to coma or even death. Despite several attempts being made, the mechanism of HAAF is yet to be clearly established. In order for the mechanism of HAAF to be elucidated, establishing a human/animal model of the phenomenon is the foremost requirement. Several research groups have attempted to reproduce the phenomenon in diabetic and nondiabetic humans and rodents and reported variable results. The success of the phenomenon is marked by a significant reduction in plasma adrenaline response to subsequent hypoglycaemic episode relative to that of the antecedent hypoglycaemic episode. A number of factors such as the insulin dosage, route of administration, fasting conditions, blood sampling methods and analyses, depth, duration, and number of antecedent hypoglycaemic episodes can impact the successful reproduction of the phenomenon and thus have to be carefully considered while developing the protocol. In this review, we have outlined the protocols followed by different research groups to reproduce the phenomenon in diabetic and nondiabetic humans and rodents including our own observations in rats and discussed the factors that have to be given careful consideration in reproducing the phenomenon successfully.